Computational methods in systems biology : 13th International Conference, CMSB 2015, Nantes, France, September 16-18, 2015, Proceedings /: 13th International Conference, CMSB 2015, Nantes, France, September 16-18, 2015, Proceedings. (2015) - Unknown
No abstract available